Les difficultés de la filière brésilienne face à la nouvelle organisation mondiale du négoce des pierres de couleur - Aurélien Reys (Confins)
The colored gemstones commoditychains, as most of natural resources exploited, have long consisted as hierarchical trades dominated by the main Western powers. Along with the growing influence of Asian countries, they are now undergoing in a major restructuring and seem to operate more like multi-polarized markets. However, countries in charge of extractive operations aren’t still realizing greatest benefits andappear to have significant troubles to participate in others processes than the ones strictly related to extracting activities. Brazil, considered as one of the world largest reserves of colored gemstones, displays an intermediate profile: it partially gets involved in the cutting stone processes but without increasing its influence or expanding its colored gemstones export revenue as it should do. In fact, local activities have now to face new competition coming from east Africa for extracting activities and Chine for cutting and trading activities. Nevertheless, with an increasing number of people reaching good standards of living through the world, the gemstones trade will probably continue to grow in the near future, keeping the door open to new opportunities for countries like Brazil, which one can count on a growing middle class that may represent soon a new chance for its gem industry.